Friedreich's Ataxia: dance and somatic education a case report - Fanny Aparecida Condé Teixeira; Bianca Christian Medeiros Sales; Elizângela Fernandes Ferreira; Elisa Almeida Costa; Luana Neves Damasceno; Eveline Torres Pereira (Universidade Estadual Paulista (UNESP), 2018)
Abstract This research aims to determine the effects of a dance program in dialogue with somatic education in psychomotor aspects in a subject with Friedreich ataxia. We used the research method intra-subject BAB design, were phase "B" comprises the treatment phase through interventions with stimuli, and "A" the stimuli are removed. We performed a dance program with 24 interventions on a subject with Friedreich Ataxia, and assessed pre- and post-program through the Monitoring Instrument Learning in Educational Dance. The results showed that the dance program with somatic education can improve the analyzed skills: getting up, sitting, shifting feet, shifting the ground, sitting position, body image, movement rhythm, and fluency movement.